Identifikasi Isolator Keramik Jenis Pasak dan Jenis Pos Saluran dengan Metode XRD dan SEM-EDX - perdana okto manik (Saintia Fisika, 2013)
A Research on identification of insulator pin types of ceramic which is oftenused as an electrical in medium and high voltage has been done.Insulator pintypes of ceramic has 40% Mullite Phase with crystal structure isOrthorombic, lattice parameters a = 7,534 Å, b = 7,678 Å, and c = 2,8814 Å;50 % Quartz Phase with crystal structure is Hexagonal, lattice parameters a =4,9332 Å, b = 4,9332 Å and c = 5,4199 Å; 10% Graphite Phase with crystalstructur is Hexagonal, lattice parameters a = 2,4548 Å and c = 6,702 Å.Microstructure of insulator pin types of ceramic has carbon (C) 10,78 %,Oxygen (O) 49,72 %, Natrium (Na) 0,54 %, Al 9,40 %, Silicon (Si) 27,41 %and Calium (K) 2,15 %.Key words : Ceramic insulator, Crystal structure, XRD and SEM-EDX